Evaluation on the Use of Online Comics among Students: Development Studies at Universitas Terbuka - Radeswandri; Vebrianto, Rian; Thahir, Musa (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2021)
Promotion is one way to spread information, so as to persuade/influence the audience to be willing to be loyal, accept, or buy towards a company or product. One form of promotional media that is effective in increasing the prospect of an object is online comics. Online comics are digital media that are dynamic and in accordance with technological developments. Based on this, this study aimed to evaluate the use of online comics among Universitas Terbuka students as a means of education and promotion. This research is development research using the ADDIE model with limitation of only on response test or evaluation of the use of online comics. The research was conducted by involving 60 students from various study programs. The data collection was done using an online questionnaire consisting of seven constructs with 34 questions related to evaluating the use of online comics. The data collected was then analyzed using SPSS version 23.00 for Windows. The results showed that the students' evaluation of the use of online comics in the seven constructs had an average of 3.11 in the